Residual lipids incorporation in a petroleum refinery. (2017) - Bezergianni, Stella; Dimitriadis, Athanasios; Chrysikou, Loukia P.
The aim of this study was to evaluate the technical feasibility and environmental benefits from integrating waste cooking oil (WCO) in a refinery, towards producing a new hybrid diesel. This new hybrid diesel, partially of fossil- and partially of bio-based origin, was evaluated as an alternative to market diesel according EN 590 specifications, showing comparable if not superior quality in the case of the former. Another scope was to compare the environmental impacts of the new hybrid diesel and the market diesel, in order to identify the most environmentally friendly fuel with the higher sustainability potential. The comparison was based on a well-to-tank (WTT) analysis including only the production processes of both fuels considered. Based on this study, the new hybrid diesel produced via co-hydroprocessing petroleum fractions with WCO presented the lower carbon foot-print, validating its sustainability superiority. It is evident that integrating residual biomass in a refinery is the most sustainable approach for incorporating biomass in the transportation sector.